XP Model for Information Systems Recording Academic Data - Janti, Suhar; Taufik, Ghofar; Komarudin, Ishak (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Fulfillment of academic information to support a decision in a college is very necessary, especially to support an academic planning and evaluation in higher education. Often management asks the student academic bureau to find out the number of students based on their class, period, number of graduates, class schedules to student grades. This encourages the student academic bureau to create a desktop-based application that can be used to find out more quickly the needs requested by management. By using the extreme programming (XP) model, it can accommodate the academic information needs of student affairs in universities in the form of a recap of academic data that can be presented in real time and quickly for the upper level management.